EFFECT OF COW TRAFFIC TYPE ON AUTOMATIC MILKING SYSTEM PERFORMANCE IN DAIRY FARMS - H. Unal; H. Kuraloglu; M. Koyuncu; K. Alibas (Journal of Animal and Plant Sciences, 2017)
The performance of automatic milking system (AMS) units on three farms with free and directed cow traffic was examined in this study. Farm A housed 123 Holstein cows and used free traffic. Farms B and C housed 104 and 102 Holstein cows, respectively, and both used milk-first-cow traffic. Daily milking frequency per cow was highest on Farm B (2.85), followed by Farm C (2.69), and Farm A (2.36). Although the daily milking rate per cow was lowest on Farm A, the daily milking yield was higher than those on the other two farms (Farm B, 25.30 kg; Farm C, 24.33 kg) with 27.33 kg. The number of daily refusals was significantly higher on Farm A (34.93) compared to refusals on the other two farms (P<0.05). The hourly milking capacities of the two AMS were lowest throughout the day on Farm A (4.4 visits), followed by Farms B and C, with 6.5 and 7.2 visits, respectively. AMS loading was higher on Farm A (78.09%) than on the other farms, which reduced the time wasted on Farm A by 15.23%. Most cows were milked two to four times daily on Farms B and C and one to two times daily on Farm A. A cow-traffic system must be chosen at the beginning of the investment. No traffic type is inherently better than any other. Farmers must be able to choose the appropriate cow traffic system for their farm, lifestyle, and labor qualification.
Keywords: Robotic milking; automatic milking system (AMS); cow traffic system; milking capacity; robotic load; milk yield; milking frequency